Optimasi Konsentrasi Pupuk Organik Cair terhadap Hasil Dua Kultivar Tanaman Selada (Lactuca sativa L.) pada Sistem Hidroponik Rakit Apung - Nefa, Atikah Julia; Sutoyo, Sutoyo; Swasti, Etti (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2022)
Lettuce (Lactuca sativa L.) is a vast horticultural plant hydroponics are grown, but improved hydroponic lettuce using Liquid Organic Fertilizer (LOF) is not optimal to replace inorganic fertilizers. The aims of this research are to determine the interaction of giving LOF with the two cultivars of lettuce, to get the optimum concentration of LOF for maximum yield base on the right concentration, and to find out the best cultivars has the best yield. This research was conducted in June to September 2019 at the Agrofarm Hidroponik 55 Cupak Tangah, Water Laboratory of Environmental Engineering Study Program, Instrumentation and Control Laboratory of Agricultural Engineering Study Program, Nutrition and Nonruminant Laboratory of Animal Husbandry Faculty, Andalas University, Padang City. The experiment used a Completely Randomized Design (CRD) consisting of 2 factors, namely lettuce cultivars (Grand Rapid and Green Coral 710) and fertilizer concentration (liquid organic fertilizer and inorganic ab-mix fertilizer) with consisted on 6 levels. There were 12 combinations and 3 replications resulting in 36 treatment units. The data were analyzed statistically using the F test at the 5% level followed by a Dunnett test. The results showed that there was no interaction between type and concentration of fertilizer with the two cultivars of lettuce. LOF being given on the lettuce products height, number of leaves, weights of plant, hardness of leaves lettuce is lower than of the one given inorganic fertilizer but LOF giving products relative level of fiber is similar to the giving inorganic fertilizer. Grand Rapid cultivars has higher and harder than Green Coral but it doesn?t show a real difference in result on weights, number of leaves and fiber?s level